Erythema Multiforme-Like Eruption Induced After Immune Checkpoint Inhibitor and Target Therapy in a Patient with Malignant Melanoma – A Case Report - Vasilev P.; Ramadan S.; Yordanova I.; Simeonov E. (Acta Medica Bulgarica)
Introduction. Erythema multiforme is an acute polyetiological hypersensitivity reaction characterized by polymorphic rashes of the skin and the mucous membranes. The triggering factors for the disease might be viral and bacterial infections, tumors, autoimmune connective tissue diseases, drugs. Immune checkpoint inhibitors are used for the treatment of multiple oncological diseases but they often cause cutaneous immune-related adverse events. Pembrolizumab is a monoclonal antibody that blocks the programmed death 1 receptor and leads to T-cytotoxic lymphocyte activation. Vemurafenib is a BRAF inhibitor which is used for the treatment of metastatic melanomas positive for BRAF V600E mutation and blocks tumor cell proliferation. Both of these agents improve survival of melanoma patients, but the modified immune condition often results in severe side effects.